2016
DOI: 10.1158/0008-5472.can-15-2194
|View full text |Cite
|
Sign up to set email alerts
|

JPO2/CDCA7L and LEDGF/p75 Are Novel Mediators of PI3K/AKT Signaling and Aggressive Phenotypes in Medulloblastoma

Abstract: Substantial evidence links Myc-PI3K/AKT signaling to the most aggressive subtype of medulloblastoma and this axis in medulloblastoma therapy. In this study, we advance understanding of how Myc-PI3K/AKT signaling contributes to this malignancy, specifically, in identifying the Myc-interacting protein JPO2 and its partner binding protein LEDGF/p75 as critical modulators of PI3K/AKT signaling and metastasis in medulloblastoma. JPO2 overexpression induced metastatic medulloblastoma in vivo through two synergistic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 50 publications
1
20
0
Order By: Relevance
“…Although R1 was first identified as a c-Myc oncoprotein interactor, little progress has been made so far in understanding its role in cancer in general and in prostate cancer specifically. Previous studies showed that R1 enhances medulloblastoma transformation with induced aggressive phenotypes (11,39) and also hepatocellular carcinoma progression (40). Our results obtained from prostate cancer are consistent with those observations, further supporting a tumor-promoting effect of R1 in cancers.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Although R1 was first identified as a c-Myc oncoprotein interactor, little progress has been made so far in understanding its role in cancer in general and in prostate cancer specifically. Previous studies showed that R1 enhances medulloblastoma transformation with induced aggressive phenotypes (11,39) and also hepatocellular carcinoma progression (40). Our results obtained from prostate cancer are consistent with those observations, further supporting a tumor-promoting effect of R1 in cancers.…”
Section: Discussionsupporting
confidence: 92%
“…These accumulated gene and pathway profiles lay the mechanistic foundations for identifying potential R1-interacting factors, given the intimate regulatory relationship between R1 and c-Myc demonstrated by other groups and by us. This idea has been coincidentally supported by recent findings of AKT activation by R1 in medulloblastoma (39). Future studies exploring the gene and signaling networks governed by R1 are merited to uncover potential unknown functions of R1 in prostate cancer.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In addition to HIV integrase, a diverse network of physiological IBD interaction partners has been discovered, including the PI3K regulator JPO2 (CDCA7L) (11)(12)(13), the zinc-finger protein POGZ (14), the cell-cycle regulator ASK (DBF4) (15), the MLL1-MENIN binary complex (16), and the transcription elongation regulator IWS1 (17). We previously revealed that all known cellular partners of the LEDGF/p75 IBD contain an intrinsically disordered IBD-binding motif (IBM) (17,18).…”
mentioning
confidence: 99%
“…Amplification of AKT3 has also been identified [81]. Additionally, a recent study demonstrated that Myc induced PI3K signaling drove a metastatic phenotype in orthotopic models [82]. …”
Section: Pi3k Pathway In Pediatric Brain Tumorsmentioning
confidence: 99%